New insights into the biogeography of south-western Europe: spatial patterns from vascular plants using cluster analysis and parsimony - Moreno Saiz, Juan Carlos (2013)
Aim: We analysed the distributional pattern of the vascular flora of the Iberian Peninsula and Balearic archipelago using cluster and parsimony methods to delineate a biogeographical scheme for south-western Europe and to compare the results with previous regionalizations. Additionally, we aim to identify areas of endemism. Location: South-western Europe (Iberian Peninsula and the Balearic Islands). Methods: Pattern analysis of a chorological dataset, consisting of the occurrences of 3041 vascular plant species in each of the 50 km × 50 km UTM cells of a grid covering Iberia and the Balearic Islands, was based on cluster analysis (unweighted pair-group method using arithmetic averages; UPGMA) and parsimony analysis of endemicity (PAE). The Jaccard similarity index was used in the UPGMA, and the set of most parsimonious trees from the PAE were summarized in a 75% majority consensus tree. Results: The UPGMA dendrogram delineated two main branches in the study region: (1) an eastern area of six sectors including the Balearic Islands plus those regions of Iberia with basic substrates, and (2) a western area with three sectors comprising the regions with acidic soils. The majority rule consensus tree of 53 most parsimonious trees from PAE showed eight main clades similarly separating eastern Iberia plus the Balearic Islands with their basic substrates, from western Iberia with its acidic and basic substrates; in addition the PAE tree showed some previously undetected chorological patterns. Main conclusions: The use of large and inclusive datasets allows for the recognition of different spatial patterns from those obtained using a limited number of endemic or indicator species. The analyses support some floristic regions previously recognized for Iberia, but not the classic Eurosiberian–Mediterranean division, and some transition territories. Our recognition of 19 areas of endemism consisting of two or more cells and 60 consisting of one cell in south-western Europe is new.